Paliperidone Reversion of Maternal Immune Activation-Induced Changes on Brain Serotonin and Kynurenine Pathways - MacDowell, Karina S.; Munarriz-Cuezva, Eva; Meana, J. Javier; Leza, Juan C.; Ortega, Jorge E. (Frontiers in Pharmacology, 2021)
Emerging evidence indicates that early-life exposure to environmental factors may increase the risk for schizophrenia via inflammatory mechanisms. Inflammation can alter the metabolism of tryptophan through the oxidative kynurenine pathway to compounds with neurotoxic and neuroprotective activity and compromise serotonin (5-HT) synthesis. Here we investigate the role of serotonergic and kynurenine pathways in the maternal immune activation (MIA) animal model of schizophrenia. The potential reversion exerted by long-term antipsychotic treatment was also evaluated. MIA was induced by prenatal administration of polyinosinic:polycytidylic acid (poly (I:C)) in mice. Expression of different proteins and the content of different metabolites involved in the function of serotonergic and kynurenine pathways was assessed by RT-PCR, immunoblot and ELISA analyses in frontal cortex of the offspring after puberty. MIA decreased tissue 5-HT content and promoted changes in the expression of serotonin transporter, 5-HT2A and 5-HT2C receptors. Expression of indoleamine 2,3-dioxygenase 2 (IDO2) and kynurenine 3-monooxygenase (KMO) was increased by poly (I:C) whereas kynurenine aminotransferase II and its metabolite kynurenic acid were not altered. Long-term paliperidone was able to counteract MIA-induced changes in 5-HT and KMO, and to increase tryptophan availability and tryptophan hydroxylase-2 expression in poly (I:C) mice but not in controls. MIA-induced increase of the cytotoxic risk ratio of kynurenine metabolites (quinolinic/kynurenic acid) was also reversed by paliperidone. MIA induces specific long-term brain effects on serotonergic activity. Such effects seem to be related with alternative activation of the kynurenine metabolic pathway towards a cytotoxic status. Atypical antipsychotic paliperodine partially remediates abnormalities observed after MIA.